(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Highway road accidents are a significant socio-economic problem, leading to loss of life, physical injuries, and financial costs. In India, highway accidents have become an alarming concern, particularly due to increasing traffic volumes, poor road conditions, inadequate law enforcement, and negligent driving. This paper seeks to explore the socio-legal factors contributing to highway road accidents, and examine the legal frameworks, societal norms, and policy interventions that can help mitigate accidents and improve road safety. The study employs a multi-dimensional approach, including legal analysis, statistical data review, and socio-behavioral perspectives, to provide recommendations for reducing highway road accidents and fostering a safer traffic environment